Exploring the Potential of Laser Ablation Carbon Isotope Analysis for Examining Ecology during the Ontogeny of Middle Pleistocene Hominins from Sima de los Huesos (Northern Spain). - Nuria Garcia; Robert S Feranec; Benjamin H Passey; Thure E Cerling; Juan Luis Arsuaga (PLoS ONE, 2015)
Laser ablation of tooth enamel was used to analyze stable carbon isotope compositions of teeth of hominins, red deer, and bears from middle Pleistocene sites in the Sierra de Atapuerca in northern Spain, to investigate the possibility that this technique could be used as an additional tool to identify periods of physiological change that are not detectable as changes in tooth morphology. Most of the specimens were found to have minimal intra-tooth variation in carbon isotopes (< 2.3‰), suggesting isotopically uniform diets through time and revealing no obvious periods of physiological change. However, one of the two sampled hominin teeth displayed a temporal carbon isotope shift (3.2‰) that was significantly greater than observed for co-occurring specimens. The δ13C value of this individual averaged about -16‰ early in life, and -13‰ later in life. This isotopic change occurred on the canine crown about 4.2 mm from the root, which corresponds to an approximate age of two to four years old in modern humans. Our dataset is perforce small owing to the precious nature of hominid teeth, but it demonstrates the potential utility of the intra-tooth isotope profile method for extracting ontogenetic histories of human ancestors.